THE IMPACT OF PRODUCTIVE ZAKAT UTILIZATION ON THE EMPOWERMENT AND WELFARE OF MSMES IN BONDOWOSO - Siti Masruroh; Izzah Dienillah; Supriyanto Supriyanto; Eko Raharto (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to test and prove empirically regarding (1) the influence of the utilization of productive zakat on the empowerment of mustahik in Badan Amil Zakat Nasional (BAZNAS) Bondowoso. (2) the influence of the utilization of productive zakat on the welfare of mustahik in Badan Amil Zakat Nasional (BAZNAS) Bondowoso. A quantitative approach with a population of 160 mustahik who have received assistance from Baznas Bondowoso with a sample of 110 respondents. The sampling method uses the Isac Micheal formula with a 5% margin of error, and uses the Simple Random Sampling method. The data collection technique uses a questionnaire with hypothesis analysis using multiple linear regression analysis. The results of the study show that (1) productive zakat has a significant effect on the empowerment of mustahik in the Badan Amil Zakat Nasional (BAZNAS) Bondowoso, (2) the utilization of productive zakat has a significant effect on the welfare of mustahik in Badan Amil Zakat Nasional (BAZNAS) Bondowoso.